Development of distributed generation assessment tool considering multi-system constraints for evaluating initial grid connection - A. Kalankul (2018)
Assessment of distributed generation (DG) is a complicated task and it is a primary importance step in designing and planning of DG installation in distribution systems. The installation of DG units at non-appropriate location and sizing can result in an increasing in power losses and violations of system constraints. In this paper, a new DG assessment tool is developed for studying and evaluating DG installations in practical distribution systems. The assessment tool is developed by writing DIgSILENT Programming Language (DPL) script in DIgSILENT PowerFactory software. The tool is used for evaluating initial grid connection of DG, considering multi-system constraints-i.e. types of DG units, location, sizing, system loading, reverse power, voltage regulation, step voltage change, short circuit level, and energy losses. Two practical distribution systems including 9-bus system and 410-bus system from Provincial Electricity Authority (PEA) of Thailand are used as case studies. Test results show that the proposed assessment tool which relies on PEA regulation of DG connection can be used to evaluate the specified DG installation. © 2011 IEEE.